Psychometric Properties of the Lasher and Faulkender Anxiety about Aging Scale (AAS) among Iranian Older Adults - Amir H. Pakpour; Shamsedin Namjoo; Khadijeh Sabahiazar; Mohammad Asghari Jafarabadi; Vijay Kumar Chattu; Hamid Allahverdipour (European Journal of Investigation in Health, Psychology and Education, 2021)
(1) Background: The older adult population of society is exposed to multiple stressors daily, such as the loss of loved ones, dysfunctional mobility, financial dependence, and suffering from numerous chronic illnesses. The present study aimed to assess the psychometric properties of the Anxiety about Aging Scale among older adults in Iran. (2) Methods: A sample of 703 community-dwelling older adults was recruited and screened using a standardized tool. The mean age of participants was 69.4 ± 8.1 years. The majority of participants were male (59.2%), married (66.6%), and illiterate (79.7%). A ‘forward-backward’ translation method was used in developing the Iranian version of the AAS for assessing the psychometric properties among older adults. Confirmatory factor analysis (CFA) and the Rasch model were used for construct validity. (3) Results: Applying CFA indicated that the model’s four original factors are the best solution, representing 55% of the total variance. The result of the CFA showed that this four-factor model had a good fit for the data. The findings were also confirmed by Rasch analysis. (4) Conclusions: The Persian version of the AAS is valid and reliable for measuring aging anxiety among Iranian older adults.